Neutrophil phenotypes implicated in the pathophysiology of post-traumatic sepsis - Mizugaki, Asumi; Wada, Takeshi; Tsuchida, Takumi; Oda, Yoshitaka; Kayano, Katsuhide; Yamakawa, Kazuma; Tanaka, Shinya (Frontiers in Medicine, 2022)
Background: The disruption of immune homeostasis after trauma is a major cause of post-traumatic organ dysfunction and/or sepsis. Recently, a variety of neutrophil phenotypes with distinct functions have been identified and suggested as involved in various clinical conditions. The association between neutrophil phenotypes and post-traumatic immunodeficiency has also been reported, yet the specific neutrophil phenotypes and their functional significance in post-traumatic sepsis have not been fully clarified. Therefore, we sought to investigate neutrophil phenotypic changes in a murine model, as these may hold prognostic value in post-traumatic sepsis. Methods: Third-degree burns affecting 25% of the body surface area were used to establish trauma model, and sepsis was induced 24 h later through cecal ligation and puncture (CLP). The Burn/CLP post-traumatic sepsis model and the Sham/CLP control model were established to assess the immunological status after trauma. Histopathological evaluation was performed on the spleen, liver, kidneys, and lung tissues. Immunological evaluation included the assessment of neutrophil markers using mass cytometry as well as cytokine measurements in serum and ascitic fluid through multiplex analysis using LUMINEX®. Results: The Burn/CLP group had a lower survival rate than the Sham/CLP group. Histopathological examination revealed an impaired immune response and more advanced organ damage in the Burn/CLP group. Furthermore, the Burn/CLP group exhibited higher levels of transforming growth factor-beta 1 in the blood and generally lower levels of cytokines than the Sham/CLP group. CD11b, which is involved in neutrophil adhesion and migration, was highly expressed on neutrophils in the Burn/CLP group. The expression of CD172a, which is related to the inhibition of phagocytosis, was also upregulated on neutrophils in the Burn/CLP group. The expression of sialic acid-binding lg-like lectin F and CD68 also differed between the two groups. Conclusion: Different neutrophil phenotypes were observed between Burn/CLP and Sham/CLP groups, suggesting that neutrophils are implicated in the immune imbalance following trauma. However, further studies are needed to prove the causal relationships with outcomes, including survival rate and organ dysfunction.